Comparative analysis of a Conventional Structure with a High-Rise Structure Considering induced Vibrational Technique A Review - Dhananjay Kushwaha; Sandeep Gupta (International Journal of Scientific Research in Civil Engineering, 2022)
In past scenario ground vibration is not considered in structures nearby to railway lanes, which causes severe damages to the structures even cause loss of life. These vibrational loading is required to settle down to provide safe designing of these structures. In past decades, the numbers of buildings constructed close to roadway or railway are increasing due to high-density urbanization and rapid development of infrastructures in urban districts. This causes some problems in surrounding structures due to the traffic-induced ground motion effect on neighboring buildings and their influences on the normal operations of high-tech facilities. The induced ground vibration cover a range of almost 2-200 Hz on the surface or underground. The vibration level generally depends on several factors such as vehicle weight and speed, suspension system and soil characteristics. This vibration caused by adjacent to the underground, ground and elevated railway systems influences on the safety of buildings, the daily life of people and the operation of high-tech devices. Therefore, it is necessary to investigate the induced vibration owning to the importance of the research field. In this paper we are presenting review of literatures related to analysis of strucures with vibrational loading.